2012
DOI: 10.1074/jbc.m111.308874
|View full text |Cite
|
Sign up to set email alerts
|

Autophosphorylation of Ser428 of EhC2PK Plays a Critical Role in Regulating Erythrophagocytosis in the Parasite Entamoeba histolytica

Abstract: Background: Novel protein kinase EhC2PK in E. histolytica is involved in initiation of erythrophagocytosis. Results: The autophosphorylation at Ser 428 position occurs through a trans-reaction and is important for stimulation of kinase activity. Conclusion: Phosphorylation at Ser428 is critical in initiation of erythrophagocytosis. Significance: It provides description of a molecular mechanism that shows importance of trans-autophosphorylation of EhC2PK in E. histolytica erythrophagocytosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…6, compare D with A). To validate these observations the levels of fluorescence in cytosol, membrane, and phagocytic cups were quantitated as described (11,48) and the results clearly showed that (Y81F)-EhCaBP1 is significantly more in the membrane region compared with the cytosol (Fig. 6E).…”
mentioning
confidence: 99%
“…6, compare D with A). To validate these observations the levels of fluorescence in cytosol, membrane, and phagocytic cups were quantitated as described (11,48) and the results clearly showed that (Y81F)-EhCaBP1 is significantly more in the membrane region compared with the cytosol (Fig. 6E).…”
mentioning
confidence: 99%
“…It has been recently demonstrated that EhCaBP1, a calcium binding protein (Jain et al ., ), the C2 domain‐containing protein kinase, EhC2PK (Somlata et al ., ) and the hypothetical protein (EHI_160980) (King et al ., ) are important regulators of erythrophagocytosis. In addition, the major haemolytic activity of E. histolytica has been associated with an alkaline phospholipase A activity (Vargas‐Villarreal et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…It appears that Ca 2+ plays a critical role as EhC2PK binds the PS-containing inner leafl et of the plasma membrane in the presence of Ca 2+ (for details about Ca 2+ signaling, see chapter on kinases and signaling). The kinase activity of EhC2PK is shown to be essential for the progression of phagocytic cups to the phagosome as overexpression of a kinasedead mutant resulted in a reduction of erythrophagocytosis [ 54 ]. Because the substrate for EhC2PK has not been identifi ed, the nature of the downstream signaling pathway propagated through EhC2PK is not clear.…”
Section: Role Of Ca 2+ In Phagocytosismentioning
confidence: 99%